A sodium ion battery negative electrode material and its preparation method and application

By performing multi-site doping and carbon composite treatment on KTOP, the problem of K-Na ion exchange of KTiOPO4 anode material in sodium ion batteries is solved, and the rapid stability of battery capacity and the extension of battery life are achieved.

CN119560559BActive Publication Date: 2025-04-18BENAN ENERGY TECH JIANGSU CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510131737.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-04-18
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

In sodium ion batteries, KTiOPO4 negative electrode material is prone to K-Na ion exchange during the charge and discharge cycle, affecting the battery life and reversible capacity.

Method used

By performing specific doping treatment on potassium titanium phosphate (KTOP), doped potassium titanium phosphate is formed, doped elements at the K and Ti positions are increased, and anionic groups are introduced to form a doped potassium titanium phosphate carbon composite material to reduce K-Na ion exchange.

Benefits of technology

The capacity of the negative electrode material of sodium ion battery is achieved quickly and stable, extending the service life of the battery, and improving the rate performance and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560559B_ABST
    Figure CN119560559B_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode material and a preparation method and application thereof, belonging to the technical field of battery material preparation. The invention prepares a sodium ion battery negative electrode material, which contains doped potassium titanyl phosphate, and the chemical formula of the doped potassium titanyl phosphate conforms to K m A x Ti 1‑y B y O(PO4) 1‑z E z , wherein A is at least one of Ca, Mg, and Ba, B is at least one of Cr, Mn, Co, Fe, Cu, V, and Zn, and E is SiO4 4‑ 、SO4 2‑ 、F ‑ , BO3 3‑ 、P2O7 4‑ At least one of, m is taken as 0.7-1.3, x is taken as 0.01-0.1, y is taken as 0.001-0.15, and z is taken as 0-0.2. The present invention performs doping at three different sites to stabilize the K ions in potassium titanium oxyphosphate, thereby alleviating the structural collapse caused by the deintercalation of K ions during use, improving the stability of the battery system, and realizing the rapid stabilization of the battery capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion battery negative electrode material and a preparation method and application thereof, belonging to the technical field of batteries. Background Art

[0002] As a key component in large-scale energy storage systems, the electrochemical performance of secondary ion batteries is particularly important. Secondary sodium ion batteries have attracted much attention due to their low cost and excellent low-temperature performance, and the electrode material directly determines the electrochemical performance of the battery.

[0003] Sodium titanium phosphate (NTP) is commonly used as the negative electrode material for sodium ion batteries. The high potential of sodium titanium phosphate comes from the fact that only Ti-OP bonds exist in this crystal structure. 3- Polyanion to Ti 4+ It has a strong inductive effect, making Ti 4+ To Ti 3+ The electrochemical redox potential corresponding to the valence change is 2.1 V (vs Na / Na + For the titanium phosphate compound ATiOPO4, since the covalency of the titanium-oxygen-titanium bond is weaker than that of the oxygen-phosphorus bond, the redox potential can be significantly reduced to 1.2-1.5 V (vs Na / Na + Among various titanium-based phosphate anode materials, KTiOPO4 (KTOP) has a larger cross-cavity and the lowest potential of KTiOPO4, which is 1.23 V, has great potential in achieving faster ion dynamics and lower cycle strain in sodium-ion batteries.

[0004] In the atomic structure of sodium titanium phosphate, titanium atoms and oxygen atoms form TiO6 octahedrons through covalent bonds. These octahedrons are connected to each other through shared vertices or edges, forming a stable three-dimensional network structure. Phosphate tetrahedrons are distributed in the network gaps formed by TiO6 octahedrons and are connected to titanium atoms through chemical bonds. Sodium ions are located in the channels of the three-dimensional skeleton formed by TiO6 octahedrons and phosphate tetrahedrons. These channels provide paths for the migration of sodium ions. This tight and orderly connection gives the sodium titanium phosphate crystal structure extremely high stability, and the chemical structure will not change with the charge and discharge cycle.

[0005] Although KTiOPO4 has a lower potential than sodium titanium phosphate, when used as a sodium ion negative electrode material, potassium ions will be replaced by sodium ions through ion exchange with sodium ions in the electrolyte during the charge and discharge cycle. This ion exchange may lead to changes in the composition and structure of the material, affecting the life and reversible capacity of the battery. Therefore, it is crucial to avoid this K-Na ion exchange through material design. Summary of the invention

[0006] In order to solve the above problems, the present invention starts from potassium titanyl phosphate (KTOP), performs specific doping treatment on it, and provides a doped potassium titanyl phosphate. The battery system prepared with this material as the negative electrode of the sodium ion battery can achieve rapid stabilization of capacity.

[0007] The first object of the present invention is to provide a negative electrode material for a sodium ion battery, wherein the negative electrode material for a sodium ion battery contains doped potassium titanyl phosphate.

[0008] The chemical formula of the doped potassium titanyl phosphate conforms to K m A x Ti 1-y B y O(PO4) 1-z E z , wherein A is at least one of Ca, Mg, and Ba, B is at least one of Cr, Mn, Co, Fe, Cu, V, and Zn, and E is SiO4 4- 、SO4 2- 、F - , BO3 3- 、P2O7 4- At least one of the following, m is between 0.7 and 1.3, x is between 0.01 and 0.1, y is between 0.001 and 0.15, and z is between 0 and 0.2.

[0009] Of course, those skilled in the art know that the values ​​of m, x, y, and z must be such that K m A x Ti 1-y B y O(PO4) 1-z E z To satisfy chemical equilibrium, that is: set the valence of A to a, the valence of B to b, and the valence of E to -c, then m+a×x+4×(1-y)+b×y-2-3(1-z)-c×z=0.

[0010] In the present invention:

[0011] (1) Doping divalent ions at the K site can effectively expand the lattice gap, create a more relaxed channel for ion migration, and thus greatly improve the ion diffusion coefficient of the material, so that the ions can quickly shuttle when the battery is charged and discharged at high rates, thereby improving the rate performance of the battery; at the same time, the unique electron cloud of the divalent ion presents a relatively dispersed and regular shape. With this characteristic, it can form a stable coordination bond with the K ion. This tight and stable binding mode is like a carefully laid out "energy anchor point" in the lattice, which strongly locks the K ion and makes its residence stability in the lattice unprecedentedly enhanced. The stability of the K ion in the lattice is greatly enhanced. Especially in the high potential state at the end of charging, the material structure is often under great pressure. At this time, this stabilization mechanism can accurately and effectively reduce the risk of structural collapse in a specific direction and slow down the occurrence of Na-K ion exchange under high pressure.

[0012] (2) The synergy between the M (M = Mn, Co, Zn, Cr...) elements doped at the Ti site and the Ti ions can produce a pinning effect, stabilizing the lattice structure. At the same time, they can interact with the divalent ions doped at the K site to form an electron cloud, which can bind the K ions and enhance the stability of the K ions in the lattice. However, when used as a negative electrode, these doped ions do not change their ion valence state and do not provide capacity. Therefore, the less the doping amount, the better.

[0013] (3) The doping of anionic groups will change the electron cloud distribution of the entire anionic group, which can enhance the electronegativity of the anionic group and reduce the discharge voltage of the negative electrode material, thereby increasing the discharge voltage of the whole battery; at the same time, when the valence of the doped polyanionic group is greater than that of the phosphate group, in order to maintain the charge balance, the chemical mechanism inside the material will drive it to accept more cations. This process is like applying an "internal force" to the originally relatively regular spatial structure of the material, causing it to slightly "distort". This seemingly small structural change contains huge energy, which creates more favorable conditions for the deintercalation of active ions.

[0014] Preferably, x is 0.01-0.1, such as 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, 0.055, 0.06, 0.065, 0.07, 0.075, 0.08, 0.085, 0.09, 0.095, 0.099, etc., including but not limited to the values ​​listed above, more preferably 0.04-0.06, and most preferably 0.05.

[0015] Preferably, y is 0.001-0.15, such as 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.145, etc., including but not limited to the values ​​listed above. More preferably, it is 0.005-0.05, and most preferably, it is 0.01.

[0016] Preferably, z is 0-0.2, more preferably z>0, such as 0.001-0.2. Such as 0.001, 0.0015, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.03, 0.05, 0.07, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.199, etc., including but not limited to the values ​​listed above. More preferably, it is 0.05-0.15, and most preferably, it is 0.1. When z=0, two sites, K site and Ti site, are doped. When z>0, three sites are doped. Both of them have significantly lower capacity stability cycles than that of only K site doping. In particular, when z>0, the number of stability cycles is almost one order of magnitude lower than that when z=0, which may be related to the synergistic effect.

[0017] Furthermore, the negative electrode material of the sodium ion battery contains a doped potassium titanyl phosphate carbon composite material, that is, the negative electrode material of the sodium ion battery also contains a carbon material, and preferably, the carbon material is coated on the surface of the doped potassium titanyl phosphate. Coating carbon on the surface of the negative electrode material has the following benefits: (1) Improving conductivity: Carbon material has good conductivity. When it is coated on the surface of the active material, it can form a continuous conductive network, promote the rapid transmission of electrons, thereby improving the conductivity of the electrode material; at the same time, carbon coating can significantly reduce the resistivity of the electrode material, which is beneficial to electron transmission. (2) Relieve volume expansion: The active material will expand in volume during the charge and discharge process. The carbon coating layer can provide a certain buffer space for this expansion, prevent the destruction of the material structure, and maintain the structural integrity of the material. (3) Improving cycle stability and rate performance: Carbon coating can promote the formation of a stable SEI film (solid electrolyte interface film), thereby enhancing the battery's charge and discharge capacity at high current density and improving rate performance. (4) Isolating the electrolyte and reducing side reactions: The carbon coating can isolate the active material from direct contact with the electrolyte, reduce the degradation of the active material surface, and thus assist in inhibiting the exchange of K-Na ions.

[0018] Furthermore, the mass ratio of the doped potassium titanium oxyphosphate to the carbon material is (0.7-0.99): (0.01-0.3), such as 0.75:0.25, 0.82:0.18, 0.9:0.1, 0.95:0.05, etc., including but not limited to the values ​​listed above. The most preferred ratio is 0.98:0.02.

[0019] The second object of the present invention is to provide a method for preparing a doped potassium titanyl phosphate carbon composite material, comprising the following steps:

[0020] S1. Mix a potassium source, a titanium source, a phosphorus source, a source A, a source B, a source E and a carbon source in proportion to obtain a precursor;

[0021] S2, heating the precursor to a set temperature under an inert gas atmosphere for heat treatment to obtain the potassium titanyl phosphate-doped carbon composite material;

[0022] Among them, the chemical formula of doped potassium titanyl phosphate conforms to K m A x Ti 1-y B y O(PO4) 1-z E z , wherein A is at least one of Ca, Mg, and Ba, B is at least one of Cr, Mn, Co, Fe, Cu, V, and Zn, and E is SiO4 4- 、SO4 2- 、F - , BO3 3- 、P2O7 4- At least one of the following, m is between 0.7 and 1.3, x is between 0.01 and 0.1, y is between 0.001 and 0.15, and z is between 0 and 0.2.

[0023] Furthermore, the ratio of the total mass of the potassium source, the titanium source, the phosphorus source, the A source, the B source, and the E source to the mass of the carbon source is (0.7-0.99): (0.01-0.3).

[0024] Furthermore, at least one of the following is included:

[0025] (1) The potassium source includes at least one of KOH, K2CO3, K2SO4, KH2PO4 and potassium acetate;

[0026] (2) The source A includes at least one of CaCO3, MgCO3 and BaSO4;

[0027] (3) The titanium source includes at least one of titanyl sulfate, TiO2, tetrabutyl titanate and titanium tetrachloride;

[0028] (4) The B source includes at least one of salt compounds or oxides of Cr, Mn, Co, Fe, Cu, V, and Zn;

[0029] (5) The phosphorus source includes at least one of H3PO4, NH4H2PO4, (NH4)2HPO4 and P2O5;

[0030] (6) The E source includes at least one of SiO2, boric acid, a phosphorus source, hydrofluoric acid and sulfuric acid;

[0031] (7) The carbon source includes at least one of acetylene black, graphite, conductive carbon black (such as Super P), sucrose and glucose.

[0032] Further, the E source is used to form polyanion BO3 3- 、P2O7 4- 、SiO3 2- 、F - or SO4 2- .

[0033] Furthermore, when E in the chemical formula is P2O7 4- When the step S1 and S2 are performed, a step of keeping the temperature at 300-400°C is included. Preferably, the keeping temperature is 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 395°C, etc., including but not limited to the listed temperatures. In the keeping temperature step, phosphate PO4 3- A dehydration reaction will occur to generate pyrophosphate P2O7 4- .

[0034] Furthermore, the insulation time is 1-10 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, etc., including but not limited to the listed time periods.

[0035] Furthermore, step S2 includes at least one of the following:

[0036] (1) The inert atmosphere includes nitrogen and / or argon;

[0037] (2) The set temperature is 700-850°C;

[0038] (3) The heating rate of the heat treatment is 1-5°C / min;

[0039] (4) The heat treatment time is 4-24 hours.

[0040] Preferably, the temperature is raised to 700-850°C and kept warm, such as 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, etc., including but not limited to the listed temperatures; the heating rate is 1-5°C / min, such as 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min, etc., including but not limited to the listed rates. The choice of heat treatment temperature directly affects the structure and properties of the material. Specifically, the sintering temperature affects the crystal structure and microstructure of the electrode material, and the sintering temperature will lead to different micromorphologies, thereby affecting the electrochemical properties of the material. Moreover, the appropriate sintering temperature can increase the specific surface area and pore volume of the material, thereby improving the discharge capacity and cycle stability.

[0041] Preferably, the duration of the heat treatment is 4-24h, such as 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, etc., including but not limited to the listed durations. Heat treatment time is also a key process parameter in the preparation process of electrode materials. Appropriate sintering time can promote grain growth in the material, improve the density and structural compactness of the material, which helps to improve the conductivity and mechanical strength of the battery. Appropriate sintering time also helps to form a good crystal structure, improve the diffusion rate of ions, improve the capacity, cycle stability and rate performance of the battery, etc., thereby improving the overall performance of the battery. Too long sintering time may cause excessive oxidation or reduction of the material surface, affecting the chemical stability and electrochemical properties of the material. Excessive sintering time will also increase energy consumption and production costs, while too short a time may cause insufficient sintering of the material, affecting the material properties.

[0042] Furthermore, in step S1, the mixing method includes one or more of dry ball milling, wet ball milling and high-speed dispersion mixing.

[0043] Furthermore, when the mixing is wet ball milling or high-speed dispersion mixing, the preparation of the precursor also includes a drying step.

[0044] Furthermore, the drying includes one or more of fluidized bed drying, spray drying and tray drying.

[0045] Furthermore, in step S2, a cooling step is also included after the heat treatment, and the cooling method includes active cooling and / or natural cooling.

[0046] Furthermore, in step S2, a crushing step is further included after the heat treatment, and the crushing method after cooling includes one or more of mechanical crushing, air flow mill crushing and disc crushing. Preferably, the particle size after crushing is D90=5-10 microns.

[0047] The third object of the present invention is to provide a sodium ion battery negative electrode material, wherein the sodium ion battery negative electrode material contains the doped potassium titanyl phosphate carbon composite material prepared by the above preparation method.

[0048] The fourth object of the present invention is to provide an application of the doped potassium titanyl phosphate carbon composite material in the preparation of a negative electrode material for a sodium ion battery.

[0049] The fifth object of the present invention is to provide a negative electrode plate, which comprises a current collector and a negative electrode active layer arranged on at least one side of the current collector along the thickness direction, and the negative electrode active layer contains the sodium ion battery negative electrode material or the doped potassium titanium phosphate carbon composite material.

[0050] Furthermore, the negative electrode active layer comprises the following components in mass percentage: 75-95% of negative electrode material, 5-15% of conductive agent and 5-15% of binder.

[0051] Furthermore, the current collector is aluminum foil, or other materials that can be used as current collectors.

[0052] Furthermore, the conductive agent used in the present invention is selected from one or more of conductive carbon black, conductive graphite, carbon nanotubes and graphene.

[0053] Furthermore, the binder can be any binder known to those skilled in the art without any particular limitation, such as chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacryloyl, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymer and guar gum copolymer. In the embodiment of the present invention, PVDF (polyvinylidene fluoride) is selected.

[0054] A sixth object of the present invention is to provide a sodium ion battery comprising the negative electrode plate.

[0055] Furthermore, the sodium ion battery also contains an electrolyte, and the electrolyte contains a sodium salt electrolyte.

[0056] Furthermore, the electrolyte can be any electrolyte well known to those skilled in the art without any particular limitation, the solvent is at least one of ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate and diethylene glycol dimethanol ether; the electrolyte salt is at least one of sodium perchlorate, sodium bis(oxalate)borate, and sodium hexafluorophosphate.

[0057] Beneficial effects of the present invention:

[0058] The present invention takes the fact that KTOP material is prone to K-Na ion exchange when used as the negative electrode material of sodium ion battery, thereby affecting the capacity stabilization speed, and realizes the inhibition of ion exchange by doping at multiple sites and optimizing the doping parameters. The prepared negative electrode material greatly reduces the number of cycles in which the battery capacity tends to be stable without negatively affecting the electrochemical properties such as specific capacity, so that the battery reaches a higher capacity level in the initial stage and maintains this level for a long time during subsequent use. Capacity stability helps to improve the energy utilization efficiency of the battery, reduce energy loss, and extend the overall service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 The charge and discharge curves of the battery system assembled with the materials obtained in Example 1.

[0060] Figure 2 The charge and discharge curves of the battery system assembled with the materials obtained in Example 1 at different rates.

[0061] Figure 3 The cycle curves of the battery system assembled with the materials obtained in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0062] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0063] The preparation method involved in the present invention is as follows:

[0064] A sodium ion battery negative electrode material K m A x Ti 1-y B y O(PO4) 1-z E z The carbon composite material is prepared by the following preparation method:

[0065] K source, A source, Ti source, B source, P source and E source are mixed according to the chemical formula molar ratio to obtain K m A x Ti 1-y B yO(PO4) 1-z E z Raw materials, then K m A x Ti 1-y B y O(PO4) 1-z E z The raw material and the carbon source material are mixed, and the solid mass ratio of the two is controlled at (0.7-0.99): (0.01-0.3). According to the solid content of 50%-80%, the mixture is evenly mixed by ball milling for 1-10 hours, and the obtained slurry is dried to obtain a precursor powder. (Optionally, the precursor powder is kept at 300-400℃ for 1-10 hours) The precursor powder is placed in a sintering kiln under an inert atmosphere (such as nitrogen and / or argon), and the sintering kiln is heated to 700-850℃ at a heating rate of 1-5℃ / min and kept at this temperature for 4-24 hours. After cooling, it is crushed to obtain K m A x Ti 1-y B y O(PO4) 1-z E z Carbon composite materials. Example 1

[0066] CaCO3 was used as Ca source, MnCO3 as Mn source, KH2PO4 as K source, P source and E source, TiO2 as Ti source and SuperP as carbon source. The ingredients were prepared according to the chemical formula molar ratio: K source: Ca source: Ti source: Mn source: P source: E source = 1.02: 0.05: 0.99: 0.01: 0.9: 0.1, K 1.02 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 The mass ratio of the raw material to the carbon source material was 0.98:0.02. The solid content was 60%. The mixture was evenly mixed by ball milling in a vertical ball mill for 4 hours. The obtained slurry was spray dried to obtain a precursor powder with good fluidity. The precursor powder was placed in a sintering kiln under a nitrogen atmosphere. The sintering kiln was heated to 350°C at a heating rate of 3°C / min and kept warm for 2 hours to complete the conversion of pyrophosphate. The temperature was then continued to rise to 700°C and kept warm for 12 hours. After natural cooling, K was obtained by air flow pulverization. 1.02 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 Carbon composite materials. Example 2

[0067] The E source was replaced with sulfuric acid, and the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source was adjusted to 0.82: 0.05: 0.99: 0.01: 0.9: 0.1. The mixture was evenly mixed by ball milling in a vertical ball mill for 4 h. The obtained slurry was spray dried to obtain a precursor powder with good fluidity. The precursor powder was placed in a sintering kiln under a nitrogen atmosphere. The sintering kiln was heated to 700° C. at a heating rate of 3° C. / min and kept warm for 12 h. The rest was the same as in Example 1 to obtain K 0.82 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.9 (SO4) 0.1 Carbon composite materials. Example 3

[0068] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 1.281: 0.01: 0.85: 0.15: 0.999: 0.001, and the rest is the same as in Example 1 to obtain K 1.281 Ca 0.01 Ti 0.85 Mn 0.15 O(PO4) 0.999 (P2O7) 0.001 Carbon composite materials. Example 4

[0069] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 1.002: 0.1: 0.999: 0.001: 0.8: 0.2, and the rest is the same as in Example 1 to obtain K 1.002 Ca 0.1 Ti 0.999 Mn 0.001 O(PO4) 0.8 (P2O7) 0.2 Carbon composite materials. Example 5

[0070] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 1.19: 0.03: 0.9: 0.1: 0.95: 0.05, and the rest is the same as in Example 1 to obtain K 1.19 Ca 0.03 Ti 0.9 Mn 0.1 O(PO4) 0.95 (P2O7) 0.05 Carbon composite materials. Example 6

[0071] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 0.96: 0.08: 0.99: 0.01: 0.9: 0.1, and the rest is the same as in Example 1 to obtain K 0.96 Ca 0.08 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 Carbon composite materials. Example 7

[0072] Source A was replaced with MgCO3, source B was replaced with CuCO3, source E was replaced with SiO2, the sintering furnace was heated to 750°C at a heating rate of 1°C / min and kept warm for 5h, the mass ratio of the doping raw material to the carbon source material was adjusted to 0.7:0.3, and the rest was the same as in Example 2, to obtain K 1.02 Mg 0.05 Ti 0.99 Cu 0.01 O(PO4) 0.9 (SiO4) 0.1 Carbon composite materials. Example 8

[0073] The A source was replaced by BaSO4, the B source was replaced by V2O5, and the E source was replaced by boric acid. The sintering furnace was heated to 780°C at a heating rate of 5°C / min and kept warm for 24h. The mass ratio of the doping raw material to the carbon source material was adjusted to 0.99:0.01. The rest was the same as in Example 2 to obtain K 0.89 Ba 0.05 Ti 0.99 V 0.01 O(PO4) 0.9 (BO3) 0.1 Carbon composite materials. Example 9

[0074] The B source was replaced by ferric oxalate, the E source was replaced by hydrofluoric acid, the sintering furnace was heated to 850°C at a heating rate of 2°C / min and kept warm for 16 hours, the mass ratio of the doping raw material to the carbon source material was adjusted to 0.8:0.2, and the rest was the same as in Example 2, to obtain K 0.72 Ba 0.05 Ti 0.99 Fe 0.01 O(PO4) 0.9 F 0.1 Carbon composite materials. Example 10

[0075] No E source was added, and the molar ratio was adjusted to K source: Ca source: Ti source: B source: P source = 0.9: 0.05: 0.99: 0.01: 1, and the rest was the same as in Example 2 to obtain K 0.92 Ca 0.05Ti 0.99 Mn 0.01 OPO4 carbon composite material. Embodiment 11

[0076] Without adding E source, B source was replaced by ZnSO4, and the molar ratio was adjusted to K source: Ca source: Ti source: B source: P source = 0.9: 0.05: 0.99: 0.01: 1, and the rest was the same as in Example 2 to obtain K 0.92 Ca 0.05 Ti 0.99 Zn 0.01 OPO4 carbon composite material. Comparative Example 1

[0077] Using K source: Ti source: P source = 1:1:1 as raw materials and the rest being the same as in Example 1, a KTiOPO4 carbon composite material was prepared. Comparative Example 2

[0078] Without adding B source and E source, the molar ratio was adjusted to K source: Ca source: Ti source: P source = 0.9: 0.05: 1: 1, and the rest was the same as in Example 1 to obtain K 0.9 Ca 0.05 TiOPO4 carbon composites. Comparative Example 3

[0079] The A source was replaced with MgCO3, the B source and the E source were not added, and the molar ratio was adjusted to K source: Ca source: Ti source: P source = 0.9: 0.05: 1: 1, and the rest was the same as in Example 1 to obtain K 0.9 Mg 0.05 TiOPO4 carbon composites. Comparative Example 4

[0080] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 0.72: 0.2: 0.99: 0.01: 0.9: 0.1, and the rest is the same as in Example 1 to obtain K 0.72 Ca 0.2 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 Carbon composite materials. Comparative Example 5

[0081] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 1.4: 0.05: 0.8: 0.2: 0.9: 0.1, and the rest is the same as in Example 1 to obtain K 1.4 Ca 0.05 Ti 0.8 Mn 0.2 O(PO4) 0.9 (P2O7)0.1 Carbon composite materials. Comparative Example 6

[0082] Adjust the molar ratio of K source: Ca source: Ti source: Mn source: P source: E source = 1.22: 0.05: 0.99: 0.01: 0.7: 0.3, and the rest is the same as in Example 1 to obtain K 1.22 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.7 (P2O7) 0.3 Carbon composite materials.

[0083] Test Case

[0084] The test method is as follows:

[0085] (1) Specific capacity test: The carbon composite material obtained in the embodiment or comparative example was used as the working electrode, and a slurry was prepared with a mass ratio of active material: acetylene black: PVDF of 8:1:1. The slurry was coated on aluminum foil, and a Na sheet was used as the counter electrode. The electrolyte used PC as the solvent and sodium hexafluorophosphate as the electrolyte salt. The specific capacity at different rates was tested.

[0086] (2) Ion diffusion coefficient test: The ion diffusion coefficient of the material is tested by the constant current intermittent titration method (GITT).

[0087] (3) Rate performance test and long cycle test: In the charge and discharge voltage range of 0-3V, the battery is charged and discharged at rates of 1C, 5C, 10C, 30C, and 50C for 5 times each, and the discharge specific capacity at different rates is recorded to test the rate performance of the battery. After that, the battery is charged and discharged for 5000 times at 10C, and a long cycle test is performed to record the number of cycles in which the battery capacity range is stable.

[0088] (4) Structural stability test: After the battery was charged and discharged for 500 cycles at 1C in the charge and discharge voltage range of 0-3V, the battery was disassembled and the working electrode was cleaned. The contents of K, Na, Ti, P, O and doping elements in the active material were tested by ICP, and the chemical formula was fitted to determine the ratio of K-Na ion exchange.

[0089] The results are as follows:

[0090] The specific capacity test results of the battery system prepared by the material obtained in Example 1 are shown in Figure 1 and Figure 2 , 1C first charge and discharge curve is as follows Figure 1 As shown, in the 0-3V charge and discharge voltage range, the K obtained in Example 1 1.02 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4)0.9 (P2O7) 0.1 The discharge specific capacity of the carbon composite material at 1C is 126 mAh / g. Figure 2 The charge and discharge curves of the assembled battery at different rates are shown, and the capacity retention rate at 50C is as high as over 80%.

[0091] Figure 3 The conventional KTiOPO4 carbon composite material (Comparative Example 1) and Example 1K 1.02 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 From the cycle curve of the carbon composite material, it can be seen that as the charge and discharge proceed, the specific capacity of the battery first increases and then tends to stabilize. This is mainly because in the charging state K 2(1-x) Na 2x The potential energy of TiOPO4 is lower than that of the reference states K2TiOPO4 and Na2TiOPO4, which indicates that K + with Na + The ion exchange is thermodynamically favorable with mixed K + / Na + The structure is more stable. In the initial stage of the charge and discharge process, part of the embedded Na ions undergo K-Na exchange (exchange with the K ions in the lattice structure, and Ti does not undergo valence changes), and part of them undergo vacancy embedding of Na ions (Ti ions undergo valence changes, providing battery capacity). As the Na-K exchange deepens, the proportion of Ti ion valence changes gradually increases, so the capacity gradually increases until it stabilizes. When it stabilizes, the Na-K exchange stops, and at this time, all reactions are Na ion deintercalation reactions. This causes the battery to require a long activation time before it can achieve stable operation. Therefore, it is necessary to conduct research on the design of materials to reduce the degree of Na-K exchange and shorten the activation time while ensuring the material capacity and the discharge medium voltage. Example 1 The inhibition of ion exchange is achieved by doping at multiple sites and optimizing the doping parameters. The prepared negative electrode material greatly reduces the number of cycles at which the battery capacity tends to stabilize without having a negative impact on electrochemical properties such as specific capacity, thereby enabling the battery to achieve a higher capacity level in the initial stage. Figure 3 Example 1 can reach a stable capacity after 17 cycles.

[0092] Table 1 Test results

[0093]

[0094] Table 1

[0095]

[0096] Table 1

[0097]

[0098] From Table 1 we can see that:

[0099] Compared with Comparative Example 1, Comparative Example 2-3 performs doping of divalent ions at the K position, which can expand the lattice gap, improve the material ion diffusion coefficient and the rate performance of the battery, and its 50C / 1C capacity ratio is 67%, which is much larger than the 36% capacity ratio of the 50C / 1C of the comparative example. The capacity of this material is basically the same as that of the comparative example. This is because the generation of capacity relies on the deintercalation of Na ions at the interstitial position, so the doping of K-position ions does not affect the capacity of the material. At the same time, since the radius of the K-position doped ions is larger than the radius of the K ions, the lattice gap is enlarged, and the potential energy of the Na ion deintercalation is degraded. At the same voltage, the replacement of Na ions and K ions is hindered, so the number of cycles at which the cycle capacity tends to be stable is reduced. At the same time, the replacement rate of Na ions is reduced from 80% in Comparative Example 1 to 60%.

[0100] Compared with Comparative Examples 2-3, Example 10-11 introduces Ti doping on the basis of K doping, and the initial specific capacity of the material decreases, but the synergy of doping Ti and B (B = Mn, Co, Zn, Cr...) elements can produce a pinning effect, stabilize the lattice structure, and strengthen the atomic bond coupling between Ti and K, and the replacement of K-Na ions is further suppressed. At the same time, due to the presence of double doping at the cation position, the strong coupling of the doped ions plays a certain role in fixing the K ions, the proportion of Na-K replacement is further reduced, the number of cycles at which the cycle capacity tends to be stable is reduced again, and the replacement rate of Na ions is reduced to 40% again.

[0101] In Examples 1 and 3-6, the polyanion group doped with P2O7 4- In Example 2, Example 7, Example 8 and Example 9, the polyanion groups are doped with SO4 2- , SiO4 4- , BO3 3- and F -From the test data, it can be seen that the three-point doped samples have an initial capacity similar to that of the control group, but the rate performance has been greatly improved. Its cycle stability number is basically close to that of normal lithium batteries, and the sodium ion replacement rate has dropped to 20%, which can meet the needs of industrial mass production. This is the result of the combined effect of multi-point doping: doping with divalent ions at the K site can expand the lattice gap, improve the material ion diffusion coefficient and the rate performance of the battery, and effectively reduce the structural collapse in a specific direction under the influence of high-voltage charge; doping at the Ti site can produce a pinning effect and stabilize the lattice structure through the synergy of doping Ti and B (M=Mn, Co, Zn, Cr...) elements. When used as a negative electrode, these doped ions do not undergo chemical changes and will not provide capacity, so the less the doping amount, the better; doping with anionic groups can enhance the electronegativity of anionic groups and reduce the discharge voltage of negative electrode materials.

[0102] From the comparison between Example 1, Example 2 and Example 3-6 and the rest of the examples, due to the sulfate and pyrophosphate P2O7 4- The electronegativity of Ti is stronger than that of phosphate. The addition of strongly electronegative anionic groups may change the reaction kinetics of the battery and optimize the electrochemical reaction process, thereby compensating for the capacity loss caused by the introduction of doping elements at the Ti position and improving the electrochemical capacity of the battery.

[0103] In Example 1, Examples 3-6 and Example 7, a high-valent anionic group (such as P2O7 4- and SiO4 4- ) can also increase more embedding sites. As can be seen from the chemical formula, more embedding potentials also mean an increase in de-embedding channels, which is beneficial to the improvement of specific capacity and rate performance. Therefore, the specific capacity and rate performance of the materials obtained in Example 1, Examples 3-6 and Example 7 are higher than those in Example 8 and Example 9.

[0104] It can be seen from Example 1 and Examples 3-6 that when the doping amount is within the protection scope of the present invention, the electrochemical performance is basically unchanged, the number of cycles at which the capacity tends to be stable is less than 100 cycles, and the replacement rate of Na ions is about 20% when the cycle is stable. However, if the doping amount is too large, such as the K-doping amount is greater than 0.1 (such as in Comparative Example 4 according to the chemical equation K 0.72 Ca 0.2 Ti 0.99 Mn 0.01 O(PO4) 0.9 (P2O7) 0.1 For material configuration, the Ti doping amount is greater than 0.15 (for example, according to the chemical formula K 1.4 Ca 0.05 Ti 0.8 Mn 0.2 O(PO4)0.9 (P2O7) 0.1 The amount of anionic groups doped is greater than 0.2 (for example, according to the chemical formula K in Comparative Example 6). 1.22 Ca 0.05 Ti 0.99 Mn 0.01 O(PO4) 0.7 (P2O7) 0.3 After mixing the ingredients), it was found that the discharge specific capacity of the obtained material was extremely low. After in-depth analysis, the main reason was attributed to the excessive content of doping elements. During the material synthesis process, the excessively high content of doping elements caused serious damage to the lattice structure of KTOP. As an important channel and supporting framework for ion deintercalation, the structural integrity of the lattice is crucial. When the KTOP lattice is destroyed, the originally ordered crystal structure becomes disordered, resulting in the obstruction or even complete blockage of the deintercalation path of Na ions. Therefore, the obtained material cannot smoothly carry out the deintercalation process of Na ions, which greatly reduces the discharge specific capacity of the material and seriously affects the actual application performance of the material in related fields such as batteries. Therefore, the content of doping elements has a certain proportional limit.

[0105] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A sodium ion battery negative electrode material, characterized in that: The sodium ion battery negative electrode material contains doped potassium titanyl phosphate; The chemical formula of the doped potassium titanyl phosphate conforms to K m A x Ti 1-y B y O(PO4) 1-z E z , wherein A is at least one of Ca, Mg, and Ba, B is at least one of Cr, Mn, Co, Fe, Cu, V, and Zn, and E is SiO4 4- 、SO4 2- 、F - , BO3 3- 、P2O7 4- At least one of the following, m is between 0.7 and 1.3, x is between 0.01 and 0.1, y is between 0.001 and 0.15, and z is between 0 and 0.

2.

2. The sodium ion battery negative electrode material according to claim 1, characterized in that Include at least one of the following characteristics: (1) The sodium ion battery negative electrode material also contains carbon material; (2)z>0。 3. The sodium ion battery negative electrode material according to claim 2, characterized in that Include at least one of the following characteristics: (1) The carbon material is coated on the surface of the doped potassium titanyl phosphate; (2) The mass ratio of the doped potassium titanyl phosphate to the carbon material is (0.7-0.99): (0.01-0.3); (3) The value of z is between 0.001 and 0.

2.

4. A method for preparing a doped potassium titanyl phosphate carbon composite material, characterized in that: The following steps are involved: S1. Mix a potassium source, a titanium source, a phosphorus source, a source A, a source B, a source E and a carbon source in proportion to obtain a precursor; S2, heating the precursor to a set temperature under an inert gas atmosphere for heat treatment to obtain the potassium titanyl phosphate-doped carbon composite material; Among them, the chemical formula of doped potassium titanyl phosphate conforms to K m A x Ti 1-y B y O(PO4) 1-z E z , wherein A is at least one of Ca, Mg, and Ba, B is at least one of Cr, Mn, Co, Fe, Cu, V, and Zn, and E is SiO4 4- 、SO4 2- 、F - , BO3 3- 、P2O7 4- At least one of the following, m is between 0.7 and 1.3, x is between 0.01 and 0.1, y is between 0.001 and 0.15, and z is between 0 and 0.

2.

5. The preparation method according to claim 4, characterized in that: Include at least one of the following characteristics: (1) The potassium source includes at least one of KOH, K2CO3, K2SO4, KH2PO4 and potassium acetate; (2) The source A includes at least one of CaCO3, MgCO3 and BaSO4; (3) The titanium source includes at least one of titanyl sulfate, TiO2, tetrabutyl titanate and titanium tetrachloride; (4) The B source includes at least one of salt compounds or oxides of Cr, Mn, Co, Fe, Cu, V, and Zn; (5) The phosphorus source includes at least one of H3PO4, NH4H2PO4, (NH4)2HPO4 and P2O5; (6) The E source includes SiO2, boric acid, and a 4- At least one of a phosphorus source, hydrofluoric acid and sulfuric acid; (7) The carbon source comprises at least one of acetylene black, graphite, conductive carbon black, sucrose and glucose; (8) The E source is used to form polyanion BO3 3- 、P2O7 4- 、SiO4 4- 、F - or SO4 2- .

6. The preparation method according to claim 4, characterized in that: In step S2, at least one of the following features is included: (1) The inert gas atmosphere includes nitrogen and / or argon; (2) The set temperature is 700-850°C; (3) The heating rate of the heat treatment is 1-5°C / min; (4) The heat treatment time is 4-24 hours.

7. The preparation method according to claim 4, characterized in that: Include at least one of the following characteristics: (1) When E in the chemical formula is P2O7 4- When the step S1 and the step S2 include a step of keeping the temperature at 300-400°C; (2) In step S1, the mixing method includes one or more of dry ball milling, wet ball milling and high-speed dispersion mixing; (3) When the mixing is wet ball milling or high-speed dispersion mixing, the preparation of the precursor further includes a drying step; (4) In step S2, a cooling step is further included after the heat treatment, and the cooling method includes active cooling and / or natural cooling; (5) In step S2, a crushing step is further included after the heat treatment, and the crushing method includes one or more of mechanical crushing, air flow mill crushing and grinding disc crushing.

8. Use of the doped potassium titanyl phosphate carbon composite material obtained by the preparation method according to any one of claims 4 to 7 in the preparation of negative electrode materials for sodium ion batteries.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises a current collector and a negative electrode active layer arranged on at least one side of the current collector along the thickness direction, and the negative electrode active layer contains the sodium ion battery negative electrode material according to any one of claims 1 to 3 or the doped potassium titanyl phosphate carbon composite material obtained by the preparation method according to any one of claims 4 to 7.

10. A sodium ion battery, characterized in that: The sodium ion battery contains the negative electrode sheet according to claim 9.

Citation Information

Patent Citations

  • Acanthosphere-shaped phosphate electrode material and preparation method thereof and lithium ion battery

    CN111072003A

  • Negative pole piece and preparation method thereof, battery and power utilization device

    CN117497768A